Temporary placement of fully covered self‐expandable metal stents for the treatment of benign biliary strictures. Issue 3 (1st June 2016) - Chaput, Ulriikka; Vienne, Ariane; Audureau, Etienne; Bauret, Paul; Bichard, Philippe; Coumaros, Dimitri; Napoléon, Bertrand; Ponchon, Thierry; Duchmann, Jean‐Christophe; Laugier, René; Lamouliatte, Hervé; Védrenne, Bruno; et al.
Abstract : Background: Endoscopic treatment of benign biliary strictures (BBS) can be challenging. Objective: To evaluate the efficacy of fully covered self‐expandable metal stents (FCSEMS) in BBS. Methods: Ninety‐two consecutive patients with BBS (chronic pancreatitis ( n  = 42), anastomotic after liver transplantation ( n  = 36), and post biliary surgical procedure ( n  = 14)) were included. FCSEMS were placed across strictures for 6 months before endoscopic extraction. Early success rate was defined as the absence of biliary stricture or as a minimal residual anomaly on post‐stent removal endoscopic retrograde cholangiopancreatography (ERCP). Secondary outcomes were the final success and stricture recurrence rates as well as procedure‐related morbidity. Results: Stenting was successful in all patients. Stenting associated complications were minor and occurred in 22 (23.9%) patients. Migration occurred in 23 (25%) patients. Stent extraction was successful in all but two patients with proximal stent migration. ERCP after the 6 months stenting showed an early success in 84.9% patients (chronic pancreatitis patients: 94.7%, liver transplant: 87.9%, post‐surgical: 61.5%) ( p  = 0.01). Final success was observed in 57/73 (78.1%) patients with a median follow‐up of 12 ± 3.56 months. Recurrence of biliary stricture occurred in 16/73 (21.9%) patients. Conclusions: FCSEMS placement is efficient for patients with BBS, in particular for chronic pancreatitis patients. Stent extraction after 6 months indwelling, although generally feasible, may fail in a few cases.